Relativistic Landau levels via Feynman-Gell-Mann formulation - Mendrot, Vitor Bentes [UNESP]; Castro, Antonio Soares de [UNESP] (My University, 2021)
Relativistic energy levels for a spin-1/2 fermion in a stationary and homogeneous magnetic field, namely the Landau levels, are obtained via the Feynman-Gell-Mann formulation of the Dirac equation using the axially symmetric gauge, such that the radial functions obey a similar equation to the one of a singular harmonic oscillator in the nonrelativistic theory.